155 Crisis leadership by medical student representatives during COVID. (16th November 2020) - Shah, Haroon Ali; Mostafa, Omar; Malik, Amman
Abstract : At the University of Birmingham, cohorts' student representatives ('Academic Representatives') are viewed as the intermediaries between staff and students; they represent views of the cohort, express concerns and work closely with the staff to tackle issues across all aspects of the medicine programme, academic and wellbeing. The collective body of medicine student representatives make the Curriculum and Wellbeing Committee (CAWC). CAWC is made up of student reps from all year groups ensuring the views of all students are conveyed to the appropriate staff groups. The COVID-19 pandemic presented an unprecedented problem for medical education. At Birmingham, the pandemic was close to the main examination period and had consequences for delivery of teaching, placements and for final year students which needed to have met the GMC's Outcome for Graduates. The pandemic caused great distress for students due to the uncertainty regarding their medical education. CAWC collated all the thoughts of the student body and provided clear and constructive student feedback to the staff ensures that contingency plans can work in the favour of the students. A staff-student meeting was held to present all the feedback we had gathered from the entire medicine cohort (2000+ students). The approach taken by CAWC was greatly welcomed by staff and student alike. Students appreciated the continual dialogue with the medical school but also being as transparent with the student cohort. Regularly informing students both on a general and year specific basis, so they were aware (within the bounds of confidentiality) as soon as we were rather than waiting for official university communication, who were under immense pressure. The CAWC committee's response to the crisis demonstrated that medical students have the tenacity and resilience to deal with challenging times, thus indicating that they can make remarkable leaders.